Allium parhamii (Amaryllidaceae, Allioideae), a new species from Central Kopet Dagh Mountains, NE Iran - Memariani, Farshid; Behroozian, Maryam; Joharchi, Mohammad Reza (Phytotaxa, 2022)
Allium parhamii is described and illustrated as a new species from the Kopet Dagh mountain range, North Khorassan province in Iran. Based on morphological features, the new species belongs to A. sect. Asteroprason. It differs from the closely related species A. monophyllum in several floral and leaf characters as well as the micromorphological characters of seed coat and karyotype. The new species is illustrated and Red-Listed as critically endangered and notes on habitats and distribution are provided.